2008
DOI: 10.1016/j.immuni.2008.07.012
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of Neutrophil Migration in Lymph Nodes during Infection

Abstract: Summary While the signals that control neutrophil migration from the blood to sites of infection have been well characterized, little is known about their migration patterns within lymph nodes, or the strategies that neutrophils use to find their local sites of action. To address these questions, we used two-photon scanning laser microscopy (TPSLM) to examine neutrophil migration in intact lymph nodes during infection with an intracellular parasite, Toxoplasma gondii. We find that neutrophils form both small, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
260
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(282 citation statements)
references
References 43 publications
20
260
1
1
Order By: Relevance
“…A46 and C49 are other NYVAC NF-B inhibitors (35, 36) whose contribution to induction of innate immune responses might be better determined by removing these We show that A52 is partially involved in DC evasion and suggest that DCs recruited after infection are involved in HIV-specific CD8 T cell and IgG responses. Neutrophils cross-prime naive T cells and induce adaptive immune responses (40,41). A52R, B15R, and K7R gene deletion enhances chemokines that can directly induce neutrophil migration, and thus HIV-specific CD8 T cell and IgG responses, which supports neutrophil mediation of HIV immune responses (18).…”
Section: Discussionmentioning
confidence: 92%
“…A46 and C49 are other NYVAC NF-B inhibitors (35, 36) whose contribution to induction of innate immune responses might be better determined by removing these We show that A52 is partially involved in DC evasion and suggest that DCs recruited after infection are involved in HIV-specific CD8 T cell and IgG responses. Neutrophils cross-prime naive T cells and induce adaptive immune responses (40,41). A52R, B15R, and K7R gene deletion enhances chemokines that can directly induce neutrophil migration, and thus HIV-specific CD8 T cell and IgG responses, which supports neutrophil mediation of HIV immune responses (18).…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies indicated that neutrophils were able to present exogenous antigen to CD8+ T-cells [7] and recent data have shown also antigen-presentation to Th1 and Th17 cells [2]. In confocal microscopic studies neutrophils migrating with fluorescently labeled pathogen were observed in draining lymph vessels [1] and lymph nodes [21]. Moreover, the chemokine receptor CCR7 has been identified as a key player in directing neutrophil migration from the interstitium to the draining lymph nodes [6].…”
Section: Interaction With Other Immune Cellsmentioning
confidence: 96%
“…Cell attachment to substrate per se may participate to the increase of immune activity and respiratory burst. In mammals, immune cells are known to migrate rapidly towards the site of infection (Abadie et al 2005;Chtanova et al 2008;Germain et al 2012). Interestingly, ex vivo explant experiments give evidence for accelerated random migration of immune cells, at rates of 8 lm min -1 , similar to interstitial velocities reported for neutrophils at sites of inflammation (Graham et al 2009;Kreisel et al 2010).…”
Section: Discussionmentioning
confidence: 68%